2020
DOI: 10.36740/wlek202009205
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Duration of Percutaneous Transhepatic Cholangiodrainage in Common Bile Duct Diseases Complicated by Obstructive Jaundice

Abstract: The aim: Is to determine the optimum duration of percutaneous transhepatic cholangiodrainage depending on the duration of obstructive jaundice and the baseline total bilirubin level in patients with benign and malignant common bile duct diseases complicated by obstructive jaundice. Materials and methods: The experience of applying percutaneous transhepatic cholangiodrainage was combined for 88 patients with common bile duct diseases complicated by obstructive jaundice. The patients were divided into three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Patients are generally discharged with tubes after their condition stabilizes to reduce costs and improve hospital efficiency 7 . Patients with benign obstruction should have their tubes indwelled for at least 12 days 8 . Patients with malignant obstructive jaundice need to wear the tube until the end of their lives 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are generally discharged with tubes after their condition stabilizes to reduce costs and improve hospital efficiency 7 . Patients with benign obstruction should have their tubes indwelled for at least 12 days 8 . Patients with malignant obstructive jaundice need to wear the tube until the end of their lives 4 .…”
Section: Introductionmentioning
confidence: 99%
“… 7 Patients with benign obstruction should have their tubes indwelled for at least 12 days. 8 Patients with malignant obstructive jaundice need to wear the tube until the end of their lives. 4 Some studies have found that PTBD patients with catheters are prone to complications such as catheter displacement, bleeding and bile leakage after surgery, and the rate of unplanned readmission within 30 days due to drainage tube dysfunction is as high as 63.9%.…”
Section: Introductionmentioning
confidence: 99%